A clinical study of ventral hernia - Jaykar, R. D.; Varudkar, A. S.; Akamanchi, Anirudh K. (International Surgery Journal, 2017)
Background: Ventral hernias are one of the most common problems confronting general surgeons. Incisional hernia is a common long-term complication of abdominal surgery and is estimated to occur in 3% to 13% of laparotomy incisions. Because there is no prospective cohort available to determine the natural history of untreated ventral hernias, most surgeons recommend that these hernias should be repaired when discovered. So, there was a need to study the disease with respect to the various presentations, to gauge the awareness levels of the patients coming to us and also to determine the best modality of treatment in our set-up. This study was done to know the proportion of ventral hernias occurring in both sexes, various age groups, various risk factors and complications of different types of ventral hernias, clinical presentations and their treatment. Methods: This was a prospective study done at our tertiary care hospital between August 2014 and August 2015 (12 months). A total number of 50 cases of anterior abdominal hernias excluding groin hernias, posterior abdominal wall hernia was studied. Data collection included a detailed history and a thorough clinical examination. Data was entered in the proforma, tabulated and analyzed using software package for statistical analysis (SPSS 2015). Results: Ventral hernia constituted 4% of all admissions to the surgical ward. Incisional hernia was the most common amongst the ventral hernias with an incidence of 46%. Infra umbilical midline was the most common site for herniation in 42% of cases followed by umbilical region in 32% of cases. Obesity and constipation were found to be the major predisposing risk factors. Small defects (<2cm) presented early with more complications. Conclusions: In the present study of ventral hernias, 50 cases of ventral hernias that were admitted to Department of Surgery in our tertiary care hospital. Ventral hernia constituted 4% of all admissions to the surgical ward. The male to female ratio was 1:1.9 The mean age was approximately 41 years. Incisional Hernia was strangulated umbilical hernia - intra operative the most common variety.